Exploiting Machine Learning Applications for Smart Grids - Gunel, Kadir; Ekti, Ali Riza (IEEE, 2019)
Machine learning methods are promising candidate to analyze and to extract features for designing Industry 4.0 based modern industrial systems which now generates huge amount of data. This data cannot he processed with conventional methods therefore, machine learning systems can play the role of the brain for the modern industrial systems especially for smart grid in which an information layer is added to the traditional electricity transmission and distribution network for data collection, storage and analysis. In this study, we discuss machine learning algorithms and give brief study on the applications for smart grid.
Keywords: Engineering